ANALYSIS THE INCREASE LEARNING OUTCOMES IN POETS SUBJECT THROUGH CTL APPROACH TO GRADE III OF STATE ELEMENTARY SCHOOL - Resty Wahyuni (Universitas Negeri Medan, 2023)
This research is entitled Analysis the Increase Learning Outcomes in Poets Subject Through CTL Approach to Grade III of State Elementary School 060807 Medan. The reason for this research is to improve the learning outcomes and learning exercises of grade III of State Elementary School 060807 Medan in learning to write poetry. This study utilized classroom research activities conducted in two cycles with student research subjects as the research method. Research information collection methods in the form of test and non-test procedure methods. At that point, the analysis in this consider used the quantitative method. The results of this study show an increase in student learning results. In the preaction test, the average value was 59.57, while in cycle I the normal value was 72.50. In this way the increment in the normal value of writing poetry from the preaction to cycle I was 12.75 points. In cycle II the normal score came to 81, an increase of 8.5 points from cycle I and 21.25 points from the preaction test. Based on the research comes about, teachers are advised to apply the Contextual Teaching and Learning (CTL) approach since it is demonstrated to progress student learning results.